Delivery Strategies for Colchicine as a Critical Dose Drug: Reducing Toxicity and Enhancing Efficacy - Yaran Lei; Yulu Yang; Guobao Yang; Ao Li; Yang Yang; Yuli Wang; Chunsheng Gao (MDPI AG, 2024)
Colchicine (COL), a widely used natural drug, has potent anti-inflammatory effects; however, as a narrow therapeutic index drug, its clinical application is limited by its serious gastrointestinal adverse effects, and only oral formulations are currently marketed worldwide. Recent studies have shown that transdermal, injection, and oral drug delivery are the three main delivery strategies for COL. This article elaborates on the research progress of different delivery strategies in terms of toxicity reduction and efficacy enhancement, depicting that the transdermal drug delivery route can avoid the first-pass effect and the traumatic pain associated with the oral and injection routes, respectively. Therefore, such a dosage form holds a significant promise that requires the development of further research to investigate effective COL delivery formulations. In addition, the permeation-promoting technologies utilized for transdermal drug delivery systems are briefly discussed. This article is expected to provide scientific ideas and theoretical guidance for future research and the exploration of COL delivery strategies.